MENINGKATKAN KEMAMPUAN ENTREPRENEURSHIP MAHASISWA PADA MATA KULIAH KEWIRAUSAHAAN DENGAN MEDIA DIGITAL PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Parozak, M Rudi Gunwan; Rosita, Fadma (LPPM Institut Pendidikan Nusantara Global, 2023)
This research discusses the application of entrepreneurship teaching to students in an effort to improve their entrepreneurial abilities. The objectives to be achieved in this research are how to determine the appropriate entrepreneur, as well as what strategies can be implemented to advance the entrepreneur being built. The type of research used is qualitative, descriptive in nature. The data collection methods used were observation, interviews and documentation. The data analysis technique is qualitative descriptive analysis, namely data reduction, data presentation, and disclosure of conclusions. The results obtained in this research were that students carried out a reset in the form of being directly involved in the practice of lpng and opening a micro-scale entrepreneur within a period of 3 weeks. Students who have been divided into small groups are all doing business in trading deals. Products marketed include processed food products, drinks and chicken eggs. There are three problems experienced by students in entrepreneurship, namely: a) limited capital; b) lack of innovation; c) low motivation and competitiveness. The strategy implemented is a digital entrepreneurial strategy, namely: Content-Based Business and Online store. Before implementing entrepreneurship in digital mode, students first conduct research on entrepreneurship directly, then take further action based on the results of the trial, and carry out entrepreneurship in digital mode